Emerging Adulthood and Identity Struggles: The Effect of Body Image on Impulsive Buying Tendencies Mediated by Self-Esteem - Prastika, Maylina Ayunda; Sa'id, Mochammad (Jurnal Sains Psikologi, 2024)
Emerging adults who are identical in their search for self-identity are prone to impulsive buying behavior. Body image, with self-esteem as a mediator, may influence the tendency to buy impulsively. Therefore, this research aims to determine how the dimensions of body image influence the tendency of impulsive buying mediated by self-esteem in 100 people aged 18–25 in Malang City. This research uses a quantitative approach with the incidental sampling technique. There are three scales used that have been adapted previously, namely the Rosenberg Self-Esteem Scale (RSES), Impulse Buying Tendency (IBT) Scale, and Multidimensional Body-Self Relations Questionnaire–Appearance Scale (MBSRQ–AS). The analysis technique used is mediation analysis with the bootstrapping method with the help of PROCESS V4.3 for SPSS software. The results show that self-esteem has a fully mediating role in the influence of one of the dimensions of body image, namely the appearance evaluation dimension, on the tendency of impulsive buying in emerging adults in Malang City. This means that emerging adults with low appearance evaluations tend to have low levels of self-esteem. Likewise, emerging adults with low self-esteem tend to engage in impulsive buying behavior. This also applies vice versa.